Trypsin detection using chitosan based fiber optic interferometric sensor - Aroor, Megha Rani (2016)
There has been remarkable developments in the field of fiber optic sensing technologies for bio-sensing applications. In this study, a novel fiber optic biosensor has been fabricated for sensing trypsin, a protease that helps in degradation of proteins to peptides. A 2 cm long No core sensor was functionalized with Nickel-Chitosan film. Chitosan, a moisture sensitive polymer acted as the chelating agent or the linker polymer which facilitated the binding of the nickel ions to trypsin. The sensor was immersed in different concentrations of trypsin sample and the spectral responses were recorded. The wavelength dips in the transmission spectrum shifted towards lower wavelengths for different concentrations of trypsin. A sensitivity of -0.09 nm μg-1ml-1 was observed for concentrations of the trypsin sample ranging from 0-200 μg ml-1.